Facial emotional expression in schizophrenia adolescents during verbal interaction with a parent - Lotzin, Annett; Haack-Dees, Barbara; Resch, Franz; Romer, Georg; Ramsauer, Brigitte (European archives of psychiatry and clinical neuroscience, 2013)
Research on emotional expression in adult schizophrenia patients has indicated an impairment of the patients’ facial expressions during social interaction. However, it is unclear whether schizophrenia adolescent-onset patients show comparable disturbances in facial expression. Our aim was to analyze facial emotions in adolescents with schizophrenia spectrum psychoses compared with non-patient controls during a problem-solving discussion with their primary caregivers. We assessed facial expressions of emotions and speaker position (speaking vs. listening) in schizophrenia and non-patient adolescents matched for age and gender. The facial emotions were coded with the Emotional Facial Action Coding System. Schizophrenia adolescents showed significantly lower rates per minute of expressions indicating positive emotions compared with non-patient adolescents (β = −0.95, 95 % CI [−1.34, −0.57], t(37.92) = −5.00, p ≤ 0.001). In contrast, there was no lower rate of expressions indicating negative emotions of schizophrenia adolescents (β = 0.10, CI [−0.42, 0.61], t(35.03) = 0.38, p = 0.709). While the negative facial expressions of non-patient adolescents were related to speaking (β = 0.63, CI [0.34, 0.92], t(26) = 4.50, p = < 0.001), this relationship was not observed in schizophrenia adolescents. Our results indicated an emotion-specific impairment of positive facial expressions in schizophrenia adolescents early in the course of illness and a deviant relation between facial emotional expressions and speech.
Published online: 14 December 2012
Gesehen am 21.05.2021